Qoraqalpog‘iston respublikasida golbol sportining rivojlanishi va O‘zbekiston chempionatlaridagi yutuqlari (SCIENCE and SOCIETY, 2026)
This article explores the development stages of goalball sport in the Republic of Karakalpakstan, focusing on athlete training and the team’s achievements in the Uzbekistan championships during 2023-2024. The athletic potential of the Karakalpakstan team is analyzed based on national competition results. The paper also highlights efforts in improving sports infrastructure, youth engagement, and support for sports among people with disabilities.